Developing global citizenship through geography education in Oman: exploring the perceptions of in-service teachers. Issue 1 (2nd January 2022) - Al-Maamari, Saif Nasser
Abstract: Based on international trends, Omani education policy increasingly charges schools with fostering active citizens who have good attributes to achieve a good future. In this article, I considered the relationship between global citizenship and geography education in Oman. In particular, the study focused on how those teachers perceive global citizenship and how it is included in Omani geography textbooks. The study employed a qualitative methodology and data obtained by conducting semi-structured interviews with eight participants. The outcomes of the study showed that geography teachers defined global citizenship as a cosmopolitan perspective that focuses on common humanity. The participants believed that educating to develop global citizens is a necessary task for the Omani geography curriculum. Yet, this curriculum is currently focusing on the cognitive dimension rather than on the behavioural dimension of global citizenship.